2023
DOI: 10.3389/fragi.2023.1292040
|View full text |Cite
|
Sign up to set email alerts
|

Markers and mechanisms of death in Drosophila

John Tower

Abstract: Parameters correlated with age and mortality in Drosophila melanogaster include decreased negative geotaxis and centrophobism behaviors, decreased climbing and walking speed, and darkened pigments in oenocytes and eye. Cessation of egg laying predicts death within approximately 5 days. Endogenous green fluorescence in eye and body increases hours prior to death. Many flies exhibit erratic movement hours before death, often leading to falls. Loss of intestinal barrier integrity (IBI) is assayed by feeding blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 121 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…The assay is simple yet nevertheless presents experimental caveats that may contribute to reproducibility issues. Two teams have reported that only a fraction of individuals turn Smurf prior to death; we feel that addressing this incongruity is best achieved through discussion with these teams, which is an avenue that lies in our future and will undeniably further reveal the unaddressed complexities of ageing ( Bitner et al, 2020 ; Landis et al, 2021 ; Tower, 2023 ). It should be recognized, however, that the Smurf assay allows the community of researchers studying ageing to use a physiological, evolutionarily conserved marker, which predicts a high risk of impending death while bringing together other so-called physiological or transcriptional hallmarks of ageing ( Rera et al, 2012 ; Clark et al, 2015 ; Dambroise et al, 2016 ; Cansell et al, 2023 ) even when death is caused by acute stresses ( Rera et al, 2012 ; Katzenberger et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The assay is simple yet nevertheless presents experimental caveats that may contribute to reproducibility issues. Two teams have reported that only a fraction of individuals turn Smurf prior to death; we feel that addressing this incongruity is best achieved through discussion with these teams, which is an avenue that lies in our future and will undeniably further reveal the unaddressed complexities of ageing ( Bitner et al, 2020 ; Landis et al, 2021 ; Tower, 2023 ). It should be recognized, however, that the Smurf assay allows the community of researchers studying ageing to use a physiological, evolutionarily conserved marker, which predicts a high risk of impending death while bringing together other so-called physiological or transcriptional hallmarks of ageing ( Rera et al, 2012 ; Clark et al, 2015 ; Dambroise et al, 2016 ; Cansell et al, 2023 ) even when death is caused by acute stresses ( Rera et al, 2012 ; Katzenberger et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%